2018
DOI: 10.1039/c8ra05432k
|View full text |Cite
|
Sign up to set email alerts
|

A cross-linking strategy with moderated pre-polymerization of resin for stereolithography

Abstract: Compared with parts fabricated via traditional methods, such as injection or compression molding, polymeric parts produced by 3D stereolithography (SLA) have poorer mechanical properties. Here, we demonstrate a cross-linking strategy used in the coating field to attain long chains for resin prepolymerization to obtain final resin parts which can expand the application of SLA. Isophorone diisocyanate (IPDI), 2-hydroxyethyl methacrylate (HEMA) and polyethylene glycol (PEG)-based prepolymer have long chains, maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…AM technology can be divided into three basic groups, namely those that are solid-based, powder-based, and liquid-based. The three most commonly used techniques are Fused Deposition Modeling (FDM) [ 4 , 5 ], Selective Laser Sintering (SLS) [ 6 , 7 ], and stereolithography (SLA) [ 8 , 9 ], where FDM is solid-based, SLS is powder-based, and SLA is liquid-based.…”
Section: Introductionmentioning
confidence: 99%
“…AM technology can be divided into three basic groups, namely those that are solid-based, powder-based, and liquid-based. The three most commonly used techniques are Fused Deposition Modeling (FDM) [ 4 , 5 ], Selective Laser Sintering (SLS) [ 6 , 7 ], and stereolithography (SLA) [ 8 , 9 ], where FDM is solid-based, SLS is powder-based, and SLA is liquid-based.…”
Section: Introductionmentioning
confidence: 99%
“…The photosensitive polymers (i.e., photopolymer) should be designed to have appropriate viscosity of less than 5 Pa•s for good fluidity and relatively high absorption coefficient, depending on the type of photoinitiators, for high printing resolution. 24 The viscosity of these photopolymers can be adjusted to a lower value by adding reactive diluent or heating the resin during the printing process. 25 Although the reactive diluent is good for viscosity control, the flexible and compressive modulus and ultimate stress gradually decline with the increase of the weight fraction of the diluent.…”
Section: Evolution Of Polymer 3d Printing History Of Polymer 3d Printingmentioning
confidence: 99%
“…However, the yield strength of the material with a smaller layer thickness was shown to be lower than that of the green after UV curing. This was because the smaller layer thickness produced a denser main network and sub-network, for which the discontinuity of the material structure easily resulted in some defects, hence affecting the continuity of the overall structure [18]. Therefore, the figure shows a lower yield strength, but the main network and sub-network had a lower density in a single unit of the specimens with a larger layer thickness, which caused fewer defects in the material and resulted in higher yield strength.…”
Section: Tensile Testmentioning
confidence: 99%
“…The results showed that the overall mechanical properties of the workpiece after thermal curing were better than that of UV curing. Ni et al [18] research 3D printing SLA technology using Hydroxyethyl Methacrylate (HEMA) as 3D printing material, by changing the printing laser intensity, testing its mechanical properties, the results show that the laser power scans at low power and high speed , leading to incomplete curing, low speed and high power may cause excessive polymerization. Ambrosio et al [19] research on 3D printing SLA technology, use resin epoxy acrylate, acrylate, methacrylate (Methacrylic Acid Esters) to print test pieces by changing the printing parameters, the results show that the factor that has the greatest impact on mechanical properties is printing orientation, UV curing time has a high impact on the chemical composition of the material.…”
Section: Introductionmentioning
confidence: 99%